Genes controlling the activation of natural killer lymphocytes are epigenetically remodeled in intestinal cells from germ‐free mice. Issue 2 (10th October 2018) - Poupeau, Audrey; Garde, Christian; Sulek, Karolina; Citirikkaya, Kiymet; Treebak, Jonas T.; Arumugam, Manimozhiyan; Simar, David; Olofsson, Louise E.; Bäckhed, Fredrik; Barrès, Romain
ABSTRACT: Remodeling of the gut microbiota is implicated in various metabolic and inflammatory diseases of the gastrointestinal tract. We hypothesized that the gut microbiota affects the DNA methylation profile of intestinal epithelial cells (IECs) which could, in turn, alter intestinal function. In this study, we used mass spectrometry and methylated DNA capture to respectively investigate global and genome‐wide DNA methylation of intestinal epithelial cells from germ‐free (GF) and conventionally raised mice. In colonic IECs from GF mice, DNA was markedly hypermethylated. This was associated with a dramatic loss of ten‐eleven‐translocation activity, a lower DNA methyltransferase activity and lower circulating levels of the 1‐carbon metabolite, folate. At the gene level, we found an enrichment for differentially methylated regions proximal to genes regulating the cytotoxicity of NK cells (false‐discovery rate < 8.9E −6 ), notably genes regulating the cross‐talk between NK cells and target cells, such as members of the NK group 2 member D ligand superfamily Raet . This distinct epigenetic signature was associated with a marked decrease in Raet1 expression and a loss of CD56 + /CD45 + cells in the intestine of GF mice. Thus, our results indicate that altered activity of methylation‐modifying enzymes in GF mice influences the IEC epigenome and modulates the crosstalk between IECs and NK cells. Epigenetic reprogramming of IECs may modulate intestinal function in diseases associated with altered gut microbiota.—Poupeau, A., Garde, C., Sulek, K., Citirikkaya, K., Treebak, J. T., Arumugam, M., Simar, D., Olofsson, L. E., Bäckhed, F., Barrès, R. Genes controlling the activation of natural killer lymphocytes are epigenetically remodeled in intestinal cells from germ‐free mice. FASEB J. 33, 2719–2731 (2019). www.fasebj.org